Microwave‐assisted foaming of polystyrene filled with carbon black; effect of filler content on foamability. (15th February 2021) - Aghvami‐Panah, Mohammad; Jamalpour, Seifollah; Ghaffarian, S. Reza
Abstract: In this work, polystyrene was filled with carbon black (CB) at 1, 3, and 5 wt% and were foamed via microwave‐assisted (MA) foaming. The composite morphology was tracked by scanning electron microscopy, transmission electron microscopy, and rheology. CB played the dominant role as the selective microwave absorbers to provide the required heat for the cell nucleation and growth. MA foaming is a controllable technique to reach proper foam density and cell size by controlling microwave energy. MA foams microstructurally were compared with the foams created via the conventional foaming procedures, including oil bath heating and fast pressure drop. One advantage of the MA method is increasing the temperature of the bulk and surface of the thick specimen simultaneously. As a result, cell nucleation and growth are uniform throughout the thick composite. Samples with a thickness of 1 cm were foamed via the MA method. Abstract :